2008
DOI: 10.1111/j.1365-2125.2008.03197.x
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate preparation for prescribing: the views of 2413 UK medical students and recent graduates

Abstract: WHAT IS ALREADY KNOWN ON THIS SUBJECT • Adverse drug events are common in National Health Service (NHS) hospitals where junior doctors take responsibility for most of the prescribing. • Safe and effective prescribing of drugs is a core competency expected of all medical graduates. • There is a perception from some of those who supervise the prescribing of drugs in the NHS that undergraduate teaching in this area may be deficient, although this view is contested. WHAT THIS STUDY ADDS • Our study suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
251
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(270 citation statements)
references
References 20 publications
10
251
0
9
Order By: Relevance
“…Eleven studies examined students' competencies regarding general prescribing 10, 21, 22, 26, 27, 28, 42, 50, 80, 81, 82. Six studies, including a large study of 2413 UK students and graduates, reported that students felt that there was a lack of learning opportunities related to rational prescribing during their medical training, and that they felt underprepared for their prescribing responsibilities 10, 22, 29, 80, 81, 82.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies examined students' competencies regarding general prescribing 10, 21, 22, 26, 27, 28, 42, 50, 80, 81, 82. Six studies, including a large study of 2413 UK students and graduates, reported that students felt that there was a lack of learning opportunities related to rational prescribing during their medical training, and that they felt underprepared for their prescribing responsibilities 10, 22, 29, 80, 81, 82.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies, including a large study of 2413 UK students and graduates, reported that students felt that there was a lack of learning opportunities related to rational prescribing during their medical training, and that they felt underprepared for their prescribing responsibilities 10, 22, 29, 80, 81, 82. Two studies, including a large multicentre study involving 895 European students, showed that students lacked essential prescribing knowledge and skills for common therapeutic problems 10, 21.…”
Section: Resultsmentioning
confidence: 99%
“…However, concerns have been expressed that medical graduates across the EU are not adequately prepared for their prescribing duties 3. In the UK, recently graduated doctors were found to be responsible for a large number of prescribing errors and reported not feeling adequately prepared for their prescribing responsibilities 4, 5. Furthermore, a recent multicenter study involving 17 European medical schools showed a general lack of essential prescribing competencies among 895 final‐year students, which has potential consequences for patient safety 6.…”
mentioning
confidence: 99%
“…The experienced or learned curriculum may differ substantially from the offered and planned curriculum, which was studied in this article [16]. UK medical students feel unprepared after graduation [9], and two other studies confirm a lacking self-confidence for two of the medical schools in this study [13,33]. It should be noted that the correlation between self-reporting confidence and performance appeared week [33].…”
Section: Discussionmentioning
confidence: 63%
“…An estimated 30 % of these errors can be attributed to insufficient knowledge and skills on the part of prescribers [7]. Medical students tend to copy the drug treatment choices of their teachers during clinical clerkships instead of basing their choices on their own independent analysis of the problem [8], which might be why junior doctors feel that they are not adequately prepared to prescribe after graduating [9]. Frail older people are at highest risk of prescribing errors because they often have multiple medical conditions for which they receive polypharmacy [6].…”
Section: Introductionmentioning
confidence: 99%